Strengthening MSMEs crafting soft skills through the implementation of system thinking business model innovation - Wahyu Andy Prastyabudi; Arda Erico Yuda; Muhammad Dzulfikar Fauzi; Arliyanti Nurdin (University of Merdeka Malang, 2022)
MSMEs have an important role in sustaining the national economy as it contributes about 60 percent of GDP. On the other hand, however, the expansion of their business is considerably low. According to an economic survey by BPS in 2016, more than 63.72 percent of MSMEs had no plan to develop their business for various reasons. In addition, the Covid-19 pandemic has turned their business increasingly sluggish, because the demand for their product sales has decreased drastically. The purpose of this community service is to empower and strengthen the business management of MSME, particularly in the crafting industry i.e. Az Zahra Creation located in Surabaya. Specifically, the program focuses on the understanding of MSMEs mindsets and improving their capability in business and financial management. The methods carried out are identifying and mapping their problems through direct observation and interviews, formulating the solution using system thinking which is then actualized in mentoring and training programs. The results of the programs are renovating the workshop room, improving MSME partners’ knowledge and skills in planning, innovation of business model, managerial, and financial management. The impact of this program is expected to exemplify for other similar MSMEs, hence, the developed framework could be adopted by others to assist the business development.